Notes on Anong, a new language - Sun, Hongkai (2024)
Through preliminary research and comparison, it has been found that the Anong language is quite different from the Nusu and Rouruo languages spoken by the Nu peoples in Bijiang and Lanping. However, it is similar to the Trung language. Therefore, I suggest that Anong and Trung should be classified as belonging to the Chingpo language branch of the Tibeto-Burman language family. In this paper, I will give a brief description of the phonology, morphology, and syntax of the Anong language as it is spoken in the Mugujia Township of Fugong County (Yunnan).